Brain Protection and Cognitive Function: Cocoa Flavonoids as Nutraceuticals - Grassi, Davide; Ferri, Claudio; Desideri, Giovambattista (Current Pharmaceutical Design, 2016)
Cognitive decline and dementia are major public health social problems, suggesting the specific need to provide research into risk factors for cognitive decline as priority topic. Increasing evidence supports the hypothesis that oxidative stress and neuroinflammation might play a crucial role in the pathophysiology of cognitive decline. Further, cognitive dysfunction and dementia in Alzheimer’s disease as well as in vascular dementia seem to be also the consequence of cerebral blood flow decrease and deregulation, also suggesting a putative pathophysiological convergence of mechanisms between atherosclerosis and Alzheimer's disease. In keeping with this, a growing interest has been addressed to flavonoids as potential nutraceuticals with neuroprotective effects. Of interest, cocoa beans have been described as a fundamental source of anti-oxidant flavonoids with the flavan-3-ols and their derivatives being present in high concentrations. Therefore, recent studies specifically focused on the favorable effects of flavonoid-rich cocoa and chocolate on cerebrovascular risk factors and cognitive function. Aim of this review is to summarize new findings concerning the cocoa effects on cognitive function, particularly focusing on some putative mechanisms of vascular and antioxidant action involved in preventing dementia.
Keywords: cocoa